EGPA presenting as sudden cardiac arrest: a case report and review of cardiac manifestations - Zhang, Huihui; Zhang, Miaolin; Yu, Tao; Zhang, Zhi; Cai, Mengyang; Wang, Gang; Zhang, Weizong; Yu, Huamin; Yuan, Hong (Frontiers in Immunology, 2026)
Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare systemic vasculitis in which cardiac involvement is a primary cause of mortality. Complete heart block presenting as Adams-Stokes syndrome is a rare but critical complication. Notably, to our knowledge, EGPA initially manifesting as Adams-Stokes syndrome has not been previously documented, based on a comprehensive review of the literature. We report a 27-year-old female presenting with recurrent syncope and seizures. Laboratory tests revealed significant eosinophilia (49.5%), and cardiac workup confirmed third-degree atrioventricular block. A diagnosis of EGPA was established based on the 2022 ACR/EULAR criteria (score=13). Emergency treatment involved temporary pacing and methylprednisolone pulse therapy, followed by mepolizumab induction. Sinus rhythm recovered within 24 hours. During a two-month follow-up, the patient maintained remission with normalized eosinophil counts and improved cardiac function. This case highlights the importance of including EGPA in the differential diagnosis of unexplained high-grade heart block and supports the efficacy of early immunosuppressive therapy in reversing life-threatening cardiac complications.